2019
DOI: 10.1109/access.2019.2958136
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Biological Highly Performance Transparent Electrodes Based on Capillary Force-Welded Hybrid AgNW Network

Abstract: Graphene/silver nanowire composite films have great potential as transparent conductive electrodes in the field of optoelectronic devices. So far, antioxidant and reducing the junction resistance are two major parameters in the silver nanowire electrode studies. In this paper, a pseudo-biological inspired structure for transparent electrodes was proposed by combining hybrid diameters silver nanowire network with the chemical vapor deposition-grown (CVD-grown) graphene as a passivation layer. Compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Because of their intrinsically high aspect ratio, high conductivity, superior optical transparency, and excellent flexibility, one-dimensional (1D) silver nanowires (AgNWs) have been extensively fabricated as flexible transparent electrodes for the development of next-generation soft wearable electronics. The electrical percolation of an AgNW network, on the other hand, is heavily dependent on the effective point contact at NW–NW junctions. The contact resistance ( R c ) at the NW–NW junction, according to Hu and colleagues, can reach 1 GΩ, which is substantially greater than the intrinsic resistance of AgNWs (260–320 Ω) . To substantially decrease R c at junctions, AgNW-based electrodes are usually post-treated with a variety of “welding” techniques, including mechanical pressing, thermal welding, plasmonic welding, chemical welding, , additives soldering, and capillary-force-induced welding, to form a compact metallic conductive network . Contrary to other techniques that require harsh conditions like destructive high temperatures, devastating pressures, or expensive apparatus, capillary-force-induced welding is a simple, rapid, room-temperature, self-limited nanowelding process. It has attracted great attention for reducing the R c in AgNW percolative networks since it can provide GPa-level pressure between two adjacent NWs. During a typical process, distributed water droplets are introduced into the nanostructures of AgNWs, and the capillary force ( F ) is induced during the drying step, effectively welding the junctions to minimize the R c . According to Liu et al, after capillary welding, the sheet resistance ( R s ) of a AgNW conductive film with an average diameter of 90 nm dramatically decreased from 2.25 × 10 5 to 179 Ω sq.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their intrinsically high aspect ratio, high conductivity, superior optical transparency, and excellent flexibility, one-dimensional (1D) silver nanowires (AgNWs) have been extensively fabricated as flexible transparent electrodes for the development of next-generation soft wearable electronics. The electrical percolation of an AgNW network, on the other hand, is heavily dependent on the effective point contact at NW–NW junctions. The contact resistance ( R c ) at the NW–NW junction, according to Hu and colleagues, can reach 1 GΩ, which is substantially greater than the intrinsic resistance of AgNWs (260–320 Ω) . To substantially decrease R c at junctions, AgNW-based electrodes are usually post-treated with a variety of “welding” techniques, including mechanical pressing, thermal welding, plasmonic welding, chemical welding, , additives soldering, and capillary-force-induced welding, to form a compact metallic conductive network . Contrary to other techniques that require harsh conditions like destructive high temperatures, devastating pressures, or expensive apparatus, capillary-force-induced welding is a simple, rapid, room-temperature, self-limited nanowelding process. It has attracted great attention for reducing the R c in AgNW percolative networks since it can provide GPa-level pressure between two adjacent NWs. During a typical process, distributed water droplets are introduced into the nanostructures of AgNWs, and the capillary force ( F ) is induced during the drying step, effectively welding the junctions to minimize the R c . According to Liu et al, after capillary welding, the sheet resistance ( R s ) of a AgNW conductive film with an average diameter of 90 nm dramatically decreased from 2.25 × 10 5 to 179 Ω sq.…”
Section: Introductionmentioning
confidence: 99%
“…To substantially decrease R c at junctions, AgNW-based electrodes are usually post-treated with a variety of “welding” techniques, including mechanical pressing, thermal welding, plasmonic welding, chemical welding, , additives soldering, and capillary-force-induced welding, to form a compact metallic conductive network . Contrary to other techniques that require harsh conditions like destructive high temperatures, devastating pressures, or expensive apparatus, capillary-force-induced welding is a simple, rapid, room-temperature, self-limited nanowelding process. It has attracted great attention for reducing the R c in AgNW percolative networks since it can provide GPa-level pressure between two adjacent NWs. During a typical process, distributed water droplets are introduced into the nanostructures of AgNWs, and the capillary force ( F ) is induced during the drying step, effectively welding the junctions to minimize the R c . According to Liu et al, after capillary welding, the sheet resistance ( R s ) of a AgNW conductive film with an average diameter of 90 nm dramatically decreased from 2.25 × 10 5 to 179 Ω sq. –1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Material stretching methods are aimed at developing devices that are stable, flexible, and self-stretchable without structural deformation. Typical flexible devices include stretchable transparent electrodes [22]- [25], thin-film transistors [26], [27], and LEDs [28]- [30]. Stretchable transparent electrodes consist of a nanowire transparent device with high conductivity and elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al reported that solution-processed MXene/AgNW-PUA transparent electrodes were used for flexible organic solar cells [ 28 ]. This method of directly covering MXene and graphene on the silver nanowire network cannot effectively solve the wire junction problem, it requires additional welding steps which limited the large-scale applications usually [ 29 , 30 ]. Therefore, it is urgently needed to prepare high-performance TCFs by adjusting the structures, composition, and preparation methods.…”
Section: Introductionmentioning
confidence: 99%